Comparison between Laser Sintering of PEEK and PA using Design of Experiment Methods - Rechtenwald, T.; Eßer, Gerd; Schmidt, Michael; Pohle, D. (Proceedings of the 3rd International WLT-conference on Lasers in Manufacturing, 2005)
PEEK (Polyetheretherketone) as well as Polyamide - the standard laser sintering material - are both semi-crystalline thermoplastics. Moreover, PEEK offers outstanding temperature resistance, mechanical strength and stiffness. PEEK possesses an outstanding chemical resistance, which leads to an excellent biocompatibility making the material a good choice especially for the manufacturing of medical instruments or even implants. Up to now these parts typically are produced by conventional manufacturing methods like injection moulding. But especially the production of individually shaped parts like implants would benefit a lot from a more flexible manufacturing technique. Laser Sintering (LS) can offer the required flexibility. Moreover, it is the most promising Rapid Prototyping Technology for the production of thermoplastic parts with a good geometrical accuracy on one hand and satisfying mechanical properties on the other. LS consequently is the ideal production technology for individual parts. It enables the direct manufacturing of products with complex geometries, including undercuts and defined porosity. Due to its high melting temperature of about 343°C laser sintering PEEK is a challenge compared to the standard polymer polyamide with a moderate melting point of about 172°C. This paper describes results on selective laser sintering of PEEK in comparison to laser sintering of the standard polymer, polyamide, using paired comparison and a full factorial design. The investigated influence coefficients on the process include the operating parameters of the laser system, the properties of the applied PEEK powder and the preheating temperature of the powder bed. Their effects on the sintering results are described and discussed in detail. © 2005 Taylor & Francis Group.
LFT Import::2019-08-05 (1196)